Food Sovereignty Practices at the Oneida Nation of Wisconsin Tsyunhehkw^ Farm: The Three Sisters, Ceremony and Community - Kruk-Buchowska, Zuzanna (Review of International American Studies, 2019)
The paper looks at the role of traditional foodways and related cultural practices in Oneida’s contemporary food sovereignty efforts, and the various understandings of the continuity of food and agricultural traditions in the community. The tribe’s Tsyunhehkw^’s (joon-hen-kwa) farm, whose name loosely translates into “life sustenance” in English, serves important cultural, economic and educational purposes. It grows Oneida white flint corn, which is considered sacred by the tribe and is used for ceremonial purposes, it grows the tobacco used for ceremonies and runs a traditional Three Sisters Garden. The Three Sisters – corn, beans and squash, are an important part of the Oneida creation story, as well as the vision of Handsome Lake – a Seneca prophet from the turn of the 19th century, who played an significant role in the revival of traditional religion among the People of the Longhouse.[1] They inform the work done at Tsyunhehkw^ to provide healthful food for the Oneida community. [1]The Oneida form part of the Iroquois Confederacy (as called by the French), referred to as the League of Five Nations by the English, or the Haudenosaunee Confederacy, as they call themselves. Haudenosaunee translates into the People of the Longhouse. The Confederacy, which was founded by the prophet known as Peacemaker with the help of Hiawatha, is made up of the Mohawks, Oneidas, Onondagas, Cayugas, and Senecas. It was intended as a way to unite the nations and create a peaceful means of decision making. The exact date of the joining of the nations is unknown and it is one of the first and longest lasting participatory democracies in the world (“About the Haudenosaunee Confederacy” 2019).